Diaspora ad astra an anthology of science fiction from the Philippines - Flores, Emil M.; Nacino, Joseph Frederick F. (Quezon City University of the Philippines Press, 2013)
Science fiction short stories.
The Malaya / Dean Francis Alfar -- Oplan Sanction / Alexander Marcos Osias -- Ina Dolor's Last Stand / Raymond P. Reyes -- The Cost of Living / Vince Torres -- A List of Things We Know / Isabel Yap -- The Keeper / Audrey Rose Villacorta -- The Day the Sexbomb Dancers Invaded Our Brains / Carljoe Javier -- Ashes / Embers / Dannah Ruth S. Ballesteros -- Rizal / Eliza Victoria -- Gene Rx / Katya Oliva-Llego -- Robots and a Slice of Pizza / Raydon L. Reyes -- Lucky / Raven Guerrero -- Space Enough and Time / Anne Lagamayo -- Taking Gaia / Celestine Trinidad -- War Zone Angel / Emil M. Flores
Keywords: Science fiction, Philippine (English)